FurRescue: A Mobile Application for Pet and Stray Animal Locator with Geo-Fencing and AI Breed Detection - Yong Huei Jean; Norfaradilla Wahid (Applied Information Technology And Computer Science, 2025)
Stray dogs and cats in Malaysia are increasingly problematic due to unspayed animals and inconsistent feeding practices. Local councils’ spay-and-return efforts are undermined by individuals feeding strays without spaying them. This complicates locating strays for adoption or reuniting lost pets with their owners, while social media posts often fail to gain sufficient visibility. The FurRescue app, developed with Visual Studio Code, Flutter, Dart, TensorFlow 2.0, and Firebase, addresses these issues by enabling users to list strays, lost, and found pets. Features include dog breed detection, geofencing, a community forum, and a chatroom for direct communication. User acceptance testing showed the app’s functionalities are effective and its UI/UX design well-received.